2015
DOI: 10.1007/s10620-015-3934-z
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon Is a Safe and Inexpensive Initial Strategy in Esophageal Food Bolus Impaction

Abstract: Glucagon is low cost, is moderately effective, and may be considered as an initial strategy. Endoscopic removal regardless of technique is safe and effective. The yield of radiography is poor in the setting of food bolus impaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…2,3,5,6 There are multiple treatment methods for esophageal food impaction, including ingestion of carbonated beverages, medications that affect esophageal motility (glucagon and nitrates most commonly), and endoscopic or surgical removal of the food bolus. [7][8][9][10][11][12] Spontaneous resolution has been reported in up to 25% of food impaction patients. Medications have been effective in nearly 40% and endoscopy in more than 95% of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,5,6 There are multiple treatment methods for esophageal food impaction, including ingestion of carbonated beverages, medications that affect esophageal motility (glucagon and nitrates most commonly), and endoscopic or surgical removal of the food bolus. [7][8][9][10][11][12] Spontaneous resolution has been reported in up to 25% of food impaction patients. Medications have been effective in nearly 40% and endoscopy in more than 95% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Medications have been effective in nearly 40% and endoscopy in more than 95% of patients. [7][8][9][10][11] Historically, removal of the food impaction by retrieval and retrograde removal by mouth has been recommended because of concern that pushing the bolus into the stomach may lead to complications in the setting of luminal narrowing. However, the push technique is likely used frequently in practice, and a recent study has suggested the technique is safe and effective.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of non-endoscopic medications and interventions are described in the current medical literature; however, all of these alternatives are associated with limited or conflicting studies on their use [4] , [5] . Examples include: butyl scopolamine [6] , [7] , glucagon [8] , [9] , benzodiazepines [10] , calcium channel blockers [11] , nitrates [12] , [13] , meat tenderizers (which has been firmly discredited and the only treatment known to cause harm) [14] , and effervescent drinks (e.g. cola) [15] .…”
Section: Introductionmentioning
confidence: 99%
“…This likely reflects concerns regarding the risks of endoscopy, preference of a minimally invasive approach to management, anecdotal reports of benefit, difficulty assimilating unplanned emergent cases within busy elective endoscopy workloads and unclear management algorithms that include multiple specialties, including emergency physicians, gastroenterology, upper GI surgery and otolaryngology. Conservative therapies for FBO include glucagon, effervescent beverages, hyoscine, benzodiazepines, glyceryl trinitrate and opiates; however, there is no high‐quality evidence to support any of these approaches and safety concerns have been raised with some …”
Section: Introductionmentioning
confidence: 99%
“…Conservative therapies for FBO include glucagon, effervescent beverages, hyoscine, benzodiazepines, glyceryl trinitrate and opiates; however, there is no high-quality evidence to support any of these approaches and safety concerns have been raised with some. 6,[12][13][14][15][16][17] Ultimately the challenge in the management of FBO is to treat patients in an effective and timely manner, relieving symptoms, identifying underlying pathology and avoiding complications. Identification of patients in whom FBO is likely to resolve spontaneously, who may therefore be suitable for elective diagnostic endoscopy, may reduce some of the burden on emergency endoscopy services, while the impact of medical therapies on this timeline is unclear.…”
Section: Introductionmentioning
confidence: 99%